IMPLEMENTASI APLIKASI E-DISASTER BERBASIS MOBILE UNTUK MENINGKATKAN KINERJA PELAPORAN BENCANA DI BPBD PROVINSI SUMATERA BARAT - Wahyuni, Ullya Mega; Kartika, Afriyanti Dwi; Akbar, Ricky; Kamil, Husnil; Akbar, Fajril; Suryamen, Haris; Hanim, Hafizah; Wenando, Febby Apri; Aziira, Aina Hubby (LPPM Universitas Andalas, 2024)
West Sumatra Province, with a high disaster risk level, requires a more efficient reporting system to support disaster management. Currently, the West Sumatra Provincial Disaster Management Agency (BPBD) relies on WhatsApp and Microsoft Excel, which are considered ineffective. The goal of this activity is to implement the mobile application E-Disaster on the Android platform to enhance disaster reporting efficiency at the BPBD of West Sumatra Province. The activity method consists of three stages: preparation, implementation, and reporting. In the preparation stage, needs analysis is conducted through visits to the BPBD of West Sumatra Province to gather necessary information for application development. Implementation involves developing the application based on the gathered requirements and conducting demonstrations and handing over the application to the BPBD of West Sumatra Province. The reporting stage involves presenting the activity results and evaluating the application usage. The outcomes show that the E-Disaster application has been successfully implemented and well-received by the BPBD of West Sumatra Province. This application facilitates BPBD officers in promptly responding to disaster reports and enhances coordination and response in the field. The conclusion drawn from this activity is that the E-Disaster application can improve the response and efficiency of the BPBD of West Sumatra Province in monitoring and responding to disasters in the region. Thus, it is expected that this application will significantly contribute to disaster management in West Sumatra Province and serve as a model for developing similar systems in other high-risk disaster areas.